Non-Performing Loan Risk Among Savings and Loan Cooperative Customers in Gowa Regency - Nurul Hajriahtul Khairiah; Wa Ode Rayyani (Jurnal Studi Multidisiplin Ilmu, 2025)
Purpose: This study analyzes the factors causing non-performing loan risk among customers of a savings and loan cooperative in Pannyangkalang Village, Gowa Regency, examined from the perspective of economic conditions and financial behavior, and formulates loan management measures the cooperative can pursue. Methodology: The study uses a qualitative case study approach. Data were collected through semi-structured interviews and observation involving customers who have experienced or are currently experiencing installment payment difficulties, together with cooperative management, and were analyzed through thematic analysis to identify patterns across cases.Results: The findings show that installment payment difficulties among cooperative customers arise from unstable seasonal income and dependence on informal financing, compounded by poor financial behavior, including the misuse of loan funds and limited household financial planning. These factors often reinforce one another, with customers affected by both experiencing the highest risk of persistent non-performing balances.Conclusions: Non-performing loan risk in this cooperative arises from the interaction between unstable economic conditions and less adaptive financial behavior, and effective mitigation requires measures addressing both dimensions simultaneously rather than treating either factor in isolation.Limitations: This study is confined to a single village and relies on qualitative interview data, so its findings are contextual and cannot be statistically generalized, nor do they quantify the relative statistical contribution of each factor to loan default.Contributions: This study highlights how economic and behavioral factors influence loan repayment capacity and provides practical implications for cooperative risk mitigation.